MODEL PELATIHAN PEMBELAJARAN KREATIF BAGI GURU SEKOLAH DASAR - Moh. Irtadji Moh. Irtadji; Tutut Chusniyah; Rumidjan Rumidjan (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: The developmental study was intended to produce the training model of creative teaching and learning which fulfilled the criteria of expediency, appropriateness, and relevance theoretically and practically. The research steps included preliminary study, planning of early form of the model, expert validation, the try out of the model, and the revision of the model. The results of the study was a model of training model of creative teaching and learning for elementary school teachers along with the guidelines and the media which had high appropriateness theoretically and practically.Keywords: training model, creative teaching and learning, elementary school teachersAbstrak: Penelitian pengembangan ini bertujuan menghasilkan model pelatihan pembelajaran kreatif, yang memenuhi kriteria kebergunaan, kelayakan, dan ketepatan secara teoritis dan praktis. Langkah-langkah penelitian meliputi studi pendahuluan, penyusunan bentuk awal model, uji ahli, uji coba model, dan revisi model. Hasil penelitian berupa model pelatihan pembelajaran kreatif bagi guruSD beserta panduan dan medianya yang memiliki tingkat keterterimaan tinggi baik secara teoritis dan praktis.Kata kunci: model pelatihan, pembelajaran kreatif, guru SD.